2024
DOI: 10.1186/s12889-024-18036-5
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to health technology adoption by older adults with chronic diseases: an integrative systematic review

Alessia Bertolazzi,
Valeria Quaglia,
Ramona Bongelli

Abstract: Background In recent years, healthcare systems have progressively adopted several technologies enhancing access to healthcare for older adults and support the delivery of efficient and effective care for this specific population. These technologies include both assistive technologies designed to maintain or improve the independence, social participation and functionality of older people at home, as well as health information technology developed to manage long-term conditions. Examples of such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 80 publications
2
1
0
Order By: Relevance
“…Although the adoption of mHealth services by older people is on the rise, their use of mHealth services is also influenced by a wide range of personal and external factors. Previous studies have found that the cost of technology is also an important factor, with limited access to broadband or other technology devices for economically disadvantaged populations further hindering access to mHealth services [50]. This is consistent with the findings of this study.…”
Section: Discussionsupporting
confidence: 93%
“…Although the adoption of mHealth services by older people is on the rise, their use of mHealth services is also influenced by a wide range of personal and external factors. Previous studies have found that the cost of technology is also an important factor, with limited access to broadband or other technology devices for economically disadvantaged populations further hindering access to mHealth services [50]. This is consistent with the findings of this study.…”
Section: Discussionsupporting
confidence: 93%
“…These recommendations are derived from the findings of the current paper, and other results from our research on end-users needs reported elsewhere [33]. As there is an overlap between our findings and those from previous research as well [55], it is also relevant to consider these recommendations when targeting older populations with other chronic diseases. The recommendations are grouped in one model that covers four aspects (see figure 1), and explained as follows:…”
Section: Recommendations For the Research On Users' Needssupporting
confidence: 53%
“…However, traditional exercise therapies necessitate on-site treatment at healthcare facilities, posing requirements in terms of time, motivation, and financial resources. Additionally, home-based exercise regimens, while economically practical, often fall short in compliance and efficacy due to challenges in supervision and resource accessibility ( Karasavvidis et al, 2020 ; Cinthuja et al, 2022 ; Bertolazzi et al, 2024 ). To address the challenges of enhancing multidimensional patient training, VR technology emerges as a promising solution ( Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%